The effectiveness of the educational preparation program from the point of view of field training students specializing in social studies - Hendawi, Manal; Nosair, Mohammad; Qadhi, Saba; Ashraah, Mamduh Menazel (Frontiers in Education, 2024)
The study aims to assess the students' views in the field training about the educational preparation program in social studies at Qatar University. The research is grounded in the adult learning theory as it involves the adult learning behaviors toward an educator preparation program. A primary quantitative research design is set up in the study to analyze the students' views. Moreover, a questionnaire is administered to gauge the opinions on six dimensions relevant to the Educational Preparation Programs (EPP). Finally, a descriptive research approach is used where the responses from 239 males and females were both included in the study (Male = 41(17.2%), (Female = 198 (82.8%students teachers are analyzed.The researchers also used interviews with 30 female students to reach their opinion about the efficiency of the teacher preparation program that they studied for 4 years at the university.According to current study results, the demographic factors do not impact the views of the field-training students in the social studies about the EPP in Qatar University. Therefore, this study recommends that teachers' self-efficacy and characteristics of EPP should be added in the dimensions for which the students' views are gauged in future studies.